The role of endothelial dysfunction and inflammation in chronic venous disease - Ana Rita Gonçalves Cardoso (2018)
Introduction - Chronic venous disease is a potentially prevalent and debilitating condition affecting millions of individuals, mostly in Western world. Predisposing genetic and environmental factors contribute to its development. However, the main etiology remains to be elucidated. Flow mediated dilation has been one of the most widely used test to evaluate the systemic endothelial function, as is non-invasive and inexpensive. As far as we know, the effect of surgical repair of varicose veins in flow mediated dilation has never been evaluated. Methods - An extensive literature search was conducted in Medline using the following key words algorithm: ("Chronic venous disease" OR "Chronic venous insufficiency" OR "varicose veins") AND ("endothelial dysfunction" OR "inflammation"). Flow mediated dilation was measured by ultrasound during reactive hyperemia in the brachial artery of patients with chronic venous disease proposed to surgical treatment (N=31), pre operatively and 6 months after surgery. Results - The difference between baseline % of flow mediated dilation (% of change) and pos-operative was not statistically significant (mean ± standard error 0,367 ± 1,585%; 95% confidence interval -3,604 to 2,870%; p=0,819). Discussion - Besides being a multifactorial disease, it is now recognized that the hallmark of chronic venous disease pathophysiology likely remains in inflammation, possibly triggered by sustained venous hypertension and valvular incompetence. Shear stress changes are directly sensed by endothelial cells, leading to its activation and subsequent recruitment of leukocytes and release of proinflammatory agents. Dysfunctional endothelium has a pivotal role perpetuating the inflammatory cascade, with consequent pathological venous changes and chronic venous disease worsening. The clinical research included in this review aimed to investigate the link between clinical significant chronic venous disease and the evidence of systemic endothelial dysfunction and its modulation by surgical treatment. However, we did not found a statistically significant difference in % of flow mediated dilation, before and 6 months after surgery. Further studies are needed to confirm our findings.